Investigating the Relationship between Nursing Technicians’ and Nursing Specialists’ Job Satisfaction, Organizational Commitment, and Turnover Intention in KSA: A Cross-Sectional Survey Study - Faten Fahad Mohammed Alharbi; AjAyEbOMeer Nasser Al Otiby; Munairh Ayadh Alshammari; Ahlam Fahad Mohammed Alharbi; Mesheal Olaywi Bashir Alanazi; Hana Hulayyil Thunayyian Alanazi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Purpose: This cross-sectional survey study aimed to investigate the relationship between job satisfaction, organizational commitment, and turnover intention among nursing technicians and nursing specialists in the Kingdom of Saudi Arabia (KSA). Methods: A total of 500 nursing staff (250 technicians, 250 specialists) from various healthcare facilities across KSA were recruited using stratified random sampling. Participants completed validated questionnaires assessing job satisfaction, organizational commitment, and turnover intention. Pearson’s correlations and multiple regression analyses were conducted to examine relationships between the variables. Results: Nursing specialists reported significantly higher levels of job satisfaction (M=3.85, SD=0.79) and organizational commitment (M=3.67, SD=0.84) compared to nursing technicians (M=3.21, SD=0.92 and M=3.08, SD=0.96 respectively), p<0.001. Turnover intention was higher among nursing technicians (M=3.55, SD=1.04) than specialists (M=2.86, SD=1.12), p<0.001. Job satisfaction and organizational commitment were significant negative predictors of turnover intention for both groups. Conclusion: Findings highlight the need for targeted interventions to improve job satisfaction and organizational commitment, especially among nursing technicians, in order to reduce turnover. Strategies such as enhancing professional development opportunities, improving work conditions, and fostering a supportive organizational climate are recommended.